Mahar Emas Dalam Pernikahan Adat Masyarakat Aceh Pidie - Muhammad Ikhsan Abdullah (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2022)
Background. Mahar is part of marriage that provided by husband to their wife, in term of Aceh mahar called mayam and consist of gold. Furthermore, each mayam is around 3gram gold for some area while the other is 3,3 gram gold. Due to the price is quite expensive at Rp. 2.500.000.- until Rp. 3.000.000.- each mayam, most of adults (man) prefer to delay their plan to marry or event married another woman from different regency, because they should prepare 15 – 30 mayam gold for getting married in other cases they are more than 30 mayam gold.Aim. In order to ensure that family have the power making decision based on their status by comparing both of Islamic law and tribe that used to be law in society.Methods. This literature study supposed to give a general view of cultural marriage in Aceh. Qualitative method is consis of field research and library research. used to collecting the data by interview numerous people that have capabilities related to research topic. combined with previous study.Results. The results of this study are that married a woman from Aceh Pidie regency is a man have to give her lots of gold well-known as mayam in Aceh culture. Generally, mahar that would be given was decided by woman family even though sometimes it was made by both families.